Habitat use and characterization of the seascape exploited by wintering adult and juvenile Southern Giant Petrels from Patagonia - Blanco, Gabriela Silvina; Pisoni, Juan Pablo; Gómez Laich, Agustina Marta; Quintana, Flavio Roberto
The characterization of the seascape used by top predators helps to understand the functioning of marine systems. The main goals of this study were to 1) analyze habitat use and at-sea movements of adult and first year juvenile southern giant petrels (SGP, Macronectes giganteus) during the austral winter, and 2) to characterize the oceanographic and biological features of their marine environment. Fil: Blanco, Gabriela Silvina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto de Biología de Organismos Marinos; Argentina Fil: Pisoni, Juan Pablo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Gómez Laich, Agustina Marta. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto de Biología de Organismos Marinos; Argentina Fil: Quintana, Flavio Roberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto de Biología de Organismos Marinos; Argentina 2nd World Seabird Conference Cape Town Sudáfrica World Seabird Union African Seabird Group